Konzultációs tájékoztató előadás az egyetem aulájában az MSZMP IX. kongresszusáról - Liebmann Béla (1966)
: Első sor: Koch Sándor; Koltay-Kastner Jenő; Szőkefalvi-Nagy Béla; …; Fodor Géza; Második sor: Kukán Ferenc; Gellért Albert; Dirner Zoltán